Loperamide for acute diarrhoea in infancy (a clinical experience) - Pitono Soeparto; Liek Djupri; Hardjono Soeparto; Haroen Noerasid (Paediatrica Indonesiana, 1981)
A total of 94 infants aged below 3 years with acute maetry diarrhoea underwent treatment with loperamide (Normotil, Pharos Indonesia). They were arbitarily divided into group I (46 patients) receiving loperamide and group II (48 patients) receiving loperamide & antibiotics in addition to oral glucose-electrolyte solution. Stools became normal within 3 days in 69.6% of patients in group I and 86% in group 11, and within 7 days in 87% of patients in group 1 and 95.4% in group Il. In 5 patients, diarrhoea worsened within 24 hours, necessitating the administration of i.v.f.d. There were no side-effects encountered during the treatment of loperamide.